DEVELOPMENT AND TESTING OF AN ANTI-TOBACCO SCHOOL-BASED CURRICULUM FOR DEAF AND HARD OF HEARING YOUTH - Berman, Barbara A. (2011)
Although school-based programming is an important element of the effort to curb tobacco use among young people, a comprehensive tailored curriculum has not been available for deaf and hard of hearing youth. The authors describe the drafting of such a program by expert educators, and findings from a test of the curriculum using a quasi-experimental non-equivalent control group design involving four schools for the deaf in three states. Two schools received the curriculum and two served as non-curriculum controls. Survey data were collected from students in grades 7–12 at baseline and at the start and end of three school years, from 511 to 616 students at each time point, to assess tobacco use, exposure to tobacco education, and tobacco-related knowledge, attitudes and practices. Changes within each school were assessed as the difference between the baseline survey and the average of the last four follow-up surveys. Current (past month) smoking declined significantly at one intervention school (22.7% baseline to 7.9% follow-up, p=.007) and current smokeless tobacco use at the other (7.5% baseline to 2.5% follow-up, p=.03). Exposure to tobacco prevention education, and anti-tobacco attitudes and knowledge each increased significantly at one or both schools. One control school experienced a significant decline in tobacco education exposure (p<.001) and an increase in anti-tobacco attitudes (p=.01). Despite limitations, this study supports that a tailored tobacco prevention curriculum can increase perceived exposure to anti-tobacco education and have a significant impact on tobacco-related practices, attitudes and knowledge among deaf and hard of hearing youth.